Influência da codopagem na luminescência persistente de cerâmicas de BaAl2O4:Eu,TR sinterizadas a laser - Silva, Deyvid do Carmo (2022)
In the last decades, the interest in materials with persistent luminescence (LP) has grown considerably, and this kind of material has been studied and improved constantly. There are countless possibilities for applications of this class of materials, from the simplest, as decoration items, to the most advanced, such as in medicine and radiation sensors. Barium aluminate (BaAl2O4) doped with some rare earth ions, in particular Europium (Eu), shows the property of LP. However, the single doping with Eu does not guarantee a long-lasting LP, and an alternative to improve this characteristic has been multiple doping. Here, we investigated the influence of codoping on the LP of BaAl2O4 ceramics doped with Eu and codoped with different rare earth (Dy, Er, Nd, Pr, and Tm). The BaAl2O4 powders were prepared by the Pechini method and the ceramics were sintered by the laser sintering method, which uses a CO2 laser as a heating source. The samples were characterized using the techniques of Differential Thermal Analysis and Thermogravimetry (DTA/TG), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Photoluminescence (PL). The laser sintered ceramics presented the main phase of BaAl2O4 with a homogeneous microstructure and high density when sintered at 1.6 W/mm2 . The ceramics exhibited PL emission at 495 nm, which is characteristic of Eu2+ in the BaAl2O4 matrix, indicating that there was an Eu valence reduction during laser sintering, even though the whole process was performed in an open atmosphere. Also, all ceramics showed persistent luminescence, visible to the naked eye for more than 15 min of a decay time. It was observed that single or double codoping plays an important role in the LP of BaAl2O4:Eu2+, making it possible to define which rare earth and their respective concentrations are more efficient. Finally, based on the results obtained, it was possible to propose a preliminary model for the LP in BaAl2O4:Eu2+ considering the insertion of two codopants.